Analisis Variasi Bahasa Pada Komunitas Di Jejaring Sosial Whatsapp: Kajian Sosiolinguistik - Hasanah, Nur; Hudiyono, Yusak; Agustian, Jaka Farih (Universitas Mulawarman, 2020)
This study aims to describe the forms of community language variations on the WhatsApp social network and describe the causes of language variations in the WhatsApp social network community. This research uses descriptive qualitative research to accurately describe the characteristics of a particular individual, condition, symptom, or group, or to determine the frequency or distribution of a symptom and other symptoms and for data analysis techniques in the form of intralinguistic equivalent method that uses things which concerns the meaning, information, context of speech as the determinant. In this study, the authors analyzed two communities, namely: 1) the Fun Futsal Samarinda community and 2) the Super Junior & ELF community. From the results of the analysis, the authors get 56 data from the speech of the two communities, which can be classified into: 1) language variations of dialect variety, 2) language variations of kolokia variety, 3) language variations of slang variety, and 4) language variations of colloquial variety. The cause of language variation in the two communities is code mixing and slang. The use of code mixing and slang is considered as a way to facilitate communication among community members.